THE DATAFICATION OF CHILDHOOD: EXAMINING CHILDREN’S AND PARENTS’ DATA PRACTICES, CHILDREN’S RIGHT TO PRIVACY AND PARENTS’ DILEMMAS - Livingstone, Sonia; Stoilova, Mariya; Nandagiri, Rishita; Milosevic, Tijana; Zdrodowska, Aldona; Mascheroni, Giovanna; Zaffaroni, Lorenzo Giuseppe; Cino, Davide; Wartella, Ellen Ann (AoIR Selected Papers of Internet Research, 2020)
In the age of continuous data collection and algorithmic predictions, children’s privacy seems threatened by the variety of surveillance and data practices in which parents, institutions, corporations and children themselves engage. The vast amount of data routinely collected about children as they grow up include data shared online, whether by children themselves (social media updates, web searches and browsing, data traces of their internet and smartphone use) or their parents (sharenting practices); data shared in the home, like conversations and environmental data captured by internet-connected devices such as smart speakers and internet connected toys; data shared outside the home, including educational and school apps, biometric data in schools and/or airports and stations, health data and medical records, geo-location apps or wearables, etc. Data can be knowingly shared with others, or “given off” as traces of online activities, and even inferred by algorithms that profile, classify and predict users’ behaviour. This panel on the datafication of childhood draws together a number of leading scholars in this area of research to explore questions and issues associated with children’s privacy online as both a protective and enabling right. The collection of papers in this panel contribute empirical data and theoretical insight on a range of relevant topics in the study of the datafication of childhood from the perspective of both children and parents. Based on qualitative and quantitative methods, the individual contributions to the panel illuminate the situated nature of data practices, their embeddedness in diverse contexts and practices of meaning-making through which children and parents negotiate online privacy.